Pengaruh Penyuluhan Tentang Kesehatan Reproduksi Remaja Terhadap Tingkat Pengetahuan Pada Siswa Di SMP 4 Satap Segeri - Alamri, Fahrial; Maharani, Citra; Syamsuriyati, Syamsuriyati; Wilma, Wilma; Basir, Muhammad; Mustamin, Mustamin (NHM PRESS, 2024)
The most important health in adolescence is reproductive health, adolescent reproductive health programs are to help adolescents to have responsible and healthy reproductive knowledge, counseling for adolescents has special problems. Adolescent reproductive health materials cover aspects of adolescent life related to reproductive health knowledge. The purpose of this study was to determine the level of knowledge of adolescent reproductive health before and after being given counseling on adolescent reproductive health in VIII students of SMPN 4 Satap Segeri. This research method is a pre-experimental research with one group pre-post design. This research was conducted at SMPN 4 Satap Segeri in 2020. The sample taken was 42 students of class VIII using the proportional simple random sampling technique. The instrument used is a questionnaire on adolescent reproductive health knowledge using presentation media. The test to determine the data analysis used the Wilcoxon non-parametric test. The results of this study indicate that the average level of knowledge of class VIII students before being given health education about adolescent reproductive health is 16.7 and the average knowledge of class VIII students after being given health education is 90.5 with a significant value of 0.000 or p <0.05. The conclusion shows the effect of health education on the level of knowledge of adolescent reproductive health in class VIII SMPN 4 Satap Segeri